Studi eksplorasi pengetahuan dan sikap terhadap kesiapsiagaan bencana banjir di SD Pilanggede Kecamatan Balen Kabupaten Bojonegoro - Fatiya Rosyida; Khofifatu Rohmah Adi (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
This study aims to determine the knowledge and attitude of flood disaster preparedness of Elementary School Pilanggede, District Balen, Bojonegoro. Knowledge is a key factor to preparedness. Knowledge can affect the attitude and awareness to standby in anticipating the disaster. Children from an early age should be given a proper understanding of the types of disasters that may be affecting their area and ways of dealing with disasters when it comes suddenly. The vulnerability of children to disasters is triggered by a limited understanding of the risks surrounding them, resulting in a lack of preparedness in the face of disasters. Elementary School Pilanggede District Balen, Bojonegoro is one that has flood every year. Not only the school buildings are flooded, but most of the students live as well. This research uses quantitative approach with survey method. The survey was conducted to find out the description of the condition of knowledge and attitude of student preparedness to the flood disaster that occurred in the environment. Furthermore, a descriptive analysis was conducted. The data needed in this research is primary data obtained from observation and spreading of questionnaire conducted at grade 3 to 6 Elementary School Pilanggede. The research findings indicate that students' knowledge of the flood disaster is still poorly proved by an understanding of the causes and occurrence of low floods. The student's attitude in reducing flood risk is also quite low as evidenced by playing during floods and the use of electronic during floods and the provision of equipment is minimal. Additional findings in this study is that there has been a study of flood disasters and how to overcome them, but not continued.Keywords: Knowledge, Attitude, Flood Preparedness http://dx.doi.org/10.17977/um022v2i12017p001